Ecologia trófica em uma taxocenose de anfíbios: estrutura, filogenia e especialização individual - Pereira, Thiago César Sena de Oliveira (2012)
Historically, ever since the pre-Darwinian naturalists interspecific competition was considered the main force responsible for structuring ecological communities. This interpretation lost strength in the late 70s and throughout the 80s giving room for other views, which consider other factors such as predation, parasitism and the phylogenetic inertia more important. Studies on changes in the trophic niche of a species are still uncommon in general and especially in amphibians. Species considered generalist might actually be a group of individual specialists, or individuals that specialize in a particular category of prey during a period of scarcity of resources, thus reducing intraspecific competition. This work studied the community structure of litter amphibians and trophic variation along the dry and rainy seasons in a population of Leptodactylus macrosternum. Sixteen-litter frog species were studied for their diet. Two central assumptions were tested: 1a) if the community is structured in the niche trophic level, and 1b) if there is a significant difference in the use of food resources by different species (i.e. if the community is structured), the observed structure is the result of ecological interactions or just the current phylogenetic inertia of species. Finally, 2) if there is variation in food resource use between seasons for L. macrosternum. The community showed a structure with respect to the use of food resources, and this structure persisted after taking into account the phylogenetic relationships among species. The diet of Leptodactylus macrosternum varied with the seasons, with a significant degree of individual specialization for the dry season. Patterns of a local community are important to understand its dynamics, and this may play a role in larger- scale processes. Therefore, the studies in community ecology are fundamental to understand and eventually restoring degraded areas